Nanodust in the Solar System: Discoveries and Interpretations - Mann, Ingrid; Meyer-Vernet, Nicole; Czechowski, Andrzej; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
Nanodust and nanometer-sized structures are important components of many objects in space. Nanodust is observed in evolved stars, young stellar objects, protoplanetary disks, and dust debris disks. Within the solar system, nanodust is observed with in-situ experiments from spacecraft. Nanometer-sized substructures are found in the collected cometary and interplanetary dust particles and in meteorites. Understanding the growth and destruction of dust, its internal evolution, as well as the optical properties and the detection of nanoparticles is of fundamental importance for astrophysical research. This book provides a focused description of the current state of research and experimental results concerning nanodust in the solar system. It addresses three major questions: What is nanodust? How was it discovered in the solar system? And how do we interpret the observations? The book serves as a self-contained reference work for space researchers and provides solid information on nanodust in cosmic environments for researchers working in astrophysics or in other fields of physics.
Nanodust in the Interstellar Medium in Comparison to the Solar System -- Phenomena of nanoparticles in relation to the Solar System -- Nanodust dynamics in interplanetary space -- Dynamics, Composition, and Origin of Jovian and Saturnian Dust Stream Particles.
Keywords: Physics; Astrophysics; Space sciences; Condensed matter; Physics; Extraterrestrial Physics, Space Sciences; Astrophysics and Astroparticles; Condensed Matter Physics; Electronic books